Effect of a small Mn and Sr deficiency on the physical properties of SrMnSb2. (2021) - Saadi, A.; Omari, L.H.; Lekdadri, A.; Lassri, H.; Boudali, A.
Abstract: Nonstoichiometric Sr1-y Mn1-z Sb2 (y ∼0.07, z ∼0.02) and its pure compound SrMnSb2 were suggested to be magnetic topological semimetals. First-principles calculations using the FP-LAPW method by means of generalized gradient approximation (GGA) have been used to investigate the structural, electronic, magnetic, thermodynamic, and thermoelectric properties of SrMnSb2, and Sr1-y Mn1-z Sb2 compounds in a temperature range from 0 K to 800 K. Our results show that small reduction of Sr and Mn atoms leads to an interesting change in their physical properties. The thermodynamic and magnetic study show that the Sr1-y Mn1-z Sb2 compound exhibits considerable thermal and magnetic behavior, while SrMnSb2 compound reveals highest transport effects.